Geography and geographers : anglo American human geography since 1945 - Johnston, R. J. (London : Edward Arnold Ltd., 1979)
Geography and Geographers provides a survey of the major debates, key thinkers and schools of thought in human geography in the English-speaking world, setting them within the context of economic, social, cultural and political as well as intellectual changes. It focuses on the debates among geographers about what their discipline should study and how that should be done, and draws on a wide reading of the geographical literature produced during a fifty-year period which is characterized by both growth in the number of academic geographers and substantial shifts in conceptions of the discipline's scientific rationale." "The pace and volume of change within the discipline shows no sign of diminishing, and this sixth edition has been extensively revised and updated to reflect both continued developments within established fields of inquiry and the introduction of significantly new approaches during the last decade. There is more material on cultural geography, 'radical approaches', and feminist geographies, alongside comprehensive coverage of recent changes across the discipline. Above all, the book maintains its traditional strength of offering a thoroughly contemporary perspective on human geography."--Jacket
Includes bibliographical references and index.
Keywords: Geography anf geographers; Human geography -- History. -- United States; Human geography -- History. -- Great Britain